The phenomenon of Type A and B personality prevalence and their correlation to the anti-health behavior of Polish physicians - Dąbek, Józefa; Wojczyk, Sławomir; Bijoch, Julia; Sierka, Oskar (Frontiers in Psychology, 2025)
ObjectivesPersonality is connected with the possible development of various diseases; therefore, the aim of this study was to assess the occurrence of Type A and B personalities and their relationship with anti-health behaviors among Polish doctors.MethodsThe study group included 823 (100%) physicians working in Poland. The study was conducted using an original questionnaire, consisting of questions regarding general data, and standardized anti-health behaviors assessment questionnaires available publicly.ResultsThe most common risk factors in the study group were: stress (545; 66.22%), insufficient sleep (375; 45.57%) and low physical activity (322; 39.17%). Physicians with Type A personality achieved higher score values on all subscales of the My Eating Habits Questionnaire than physicians with intermediate and Type B personalities.ConclusionThe occurrence of Type A personality was associated with, among others, worse eating habits, more frequent sleep deprivation, and exposure to stress and low physical activity. There is a need to conduct educational activities at an early school stage regarding the benefits of following healthy lifestyle recommendations, and consequently limiting the development of diseases and their complications.